Some Aspects of the Students’ Musical Leisure as the Way of Outlook Position Forming in the Conditions of the Eastern Carpathians - Klepar, Maria; Chervinska, Inna (Journal of Vasyl Stefanyk Precarpathian National University, 2014)
The main problem resolution for the upbringing of the youth in complicated modern social-economic conditions of the Eastern Carpathians needs the universal scientific comprehension of history theory and practice of national pedagogy, the recognition of the main subject roles in educational extension, the institutions for young personality socialization within the leasure occupies the main place. The meaningful leasure organization and using it in humanistic education has the main practical meaning.